Conceptualising innovation and professional learning in the Hong Kong context. Issue 1 (2nd January 2021) - Lu, Jiafang; Campbell, Paul
ABSTRACT: In this paper, we review the challenges of sustaining effective teacher professional learning in Hong Kong and propose that professional learning could enable teacher innovation, and teacher innovation reversely rejuvenates professional learning. We also argue that greater exploration is needed of how professional learning is theorised in relation to broader themes that influence it. These key themes explored have significant implications for both organisational and wider systemic culture and practice both in Hong Kong and in systems around the world.